Endovascular Treatment of Brain Arteriovenous Malformations in Pediatric Patients: A Single Center Experience and Review of the Literature - Borges de Almeida, Gonçalo; Pamplona, Jaime; Baptista, Mariana; Carvalho, Rui; Conceição, Carla; Lopes da Silva, Rita; Sagarribay, Amets; Reis, João; Fragata, Isabel (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2023)
Background Brain arteriovenous malformations (bAVMs) are abnormal vascular connections with direct arteriovenous shunts, generally symptomatic in the adult life. However, a small number of bAVMs may manifest in pediatric patients, with higher bleeding risk and mortality rates when compared to adults. The purpose of this study is to review our experience with endovascular treatment of bAVMs in pediatric patients.Methods This is a retrospective analysis of all bAVMs in pediatric patients (0–18 years) who underwent diagnostic digital subtraction angiography (DSA) at our institution from January 2010 to June 2021.Results Twenty-six patients met the inclusion criteria, of which 12 underwent endovascular treatment. Treated patients had a mean age of 10.25 years and 58% were females. Complete angiographic exclusion was achieved in five (42%) patients with endovascular treatment. Five patients with residual bAVM after embolization needed adjuvant therapy with surgery (n = 3) or stereotactic radiosurgery (SRS; n = 2). Two patients are still undergoing embolization sessions. Procedure-related complications occurred in two patients (17%) and included small vessel perforation and an occipital ischemic stroke. Two patients showed bAVM recurrence on follow-up (17%) and subsequently underwent SRS (n = 1) or surgery (n = 1), both resulting in complete bAVM exclusion. All patients had a modified Rankin scale (mRS) score of 0 to 2 on follow-up.Conclusion Our experience supports the effectiveness and safety of endovascular treatment of bAVM in selected pediatric patients. A multidisciplinary approach combining surgery and SRS is warranted to achieve higher complete bAVM obliteration rates. Long-term follow-up is important as these lesions may show recurrence over time, especially in the pediatric population.
Keywords: pediatric brain arteriovenous malformations; intracranial hemorrhage; endovascular embolization